PHILOSOPHICAL ANALYSIS VALUE LEVEL OF PERCEPTION OF THE WORLD - S. I. Nekrasov; A. V. Novikova (Научный вестник МГТУ ГА, 2016)
The article is devoted to the philosophical understanding of the problem of perception of values and antivalues. Beliefs, recognized among the people regarding the purposes to which it is important to strive for life, named values. They are the Foundation for moral principles and provide people with their human existence despite the fact that different cultures hold different principles. In the tribe Yanomami cruelty is considered a value. The expectation that men will defend their honor in combat, is to be the norm corresponding to this value. Anyway, the principles followed by the personality, are accounted for morality. Principles justify the norms and standards that support human being in his desire to be honest and sincere for that society in which he lives, and be worthy of its representative.